Spirit and story: Pentecostal readings of scripture : essays in honor of John Christopher Thomas - Charette, Blaine; Waddell, Robby; Thomas, John Christopher (New Testament monographs, 2020)
This collection of essays brings together an international group of biblical scholars, theologians, and historians who are committed to readings of biblical texts that are sensitive to the work of the Spirit. Perhaps no one has contributed more in recent decades to the description and promotion of Pentecostal Theology than Chris Thomas, and this volume serves as a loving and respectful tribute to his commitment and achievement.--Thomas's own work on the story told in the gospel and letters of John as well as his explorations into the narrative structure of the Apocalypse are models not only of exegetical proficiency but also of the careful elucidation of the text for the general reader as well as the expert. Moreover, his work is distinguished by prayerful pastoral commitment as his ear is consistently attentive to what the Spirit is saying to the church.--The influence of Chris Thomas has been very considerable. The essays presented here capture the scope of his interests and of his important contribution to both the church and the academy. -- Publisher